Tinjauan Hukum Islam Terhadap Tradisi Mayangi di Desa Puger Wetan Kecamatan Puger Kabupaten Jember - Via Nailatul Husna (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
The Mayangi tradition in Puger Wetan Village is a tradition passed down from generation to generation from ancient Javanese society, until now it is still widely found in Javanese life, especially in Puger Wetan Village, Puger District, Jember Regency. The focus of the problems examined in these theses are; (1) How is The Mayangi Tradition Implementation Mechanism in Puger Wetan Village, Puger District, Jember Regency? (2) How to Review Islamic Law Against MayangiTradition? This research uses qualitative research by conducting field research supported by library researchers. The results showed that: (1) The implementation ofThe Mayangi tradition in Puger Wetan Village, Puger Subdistrict, Jember Regency, is usually carried out before the wedding and when the Sukerta child has grown up. (2)The Mayangi tradition is motivated by the existence of special born children or Sukerta children, Sukerta children if they are not treated, bad luck will always suffer in their life. (3) The implementation of The Mayangi tradition includes Urf Sahih if it is done as a form of gratitude to Allah SWT.